The effect of sulphate and phosphate ions on Cr(VI) reduction by Streptomyces sp. MC1, including studies of growth and pleomorphism - Villegas, Liliana Beatriz (2013)
To help address conflicting opinions regarding the ability of chromate ions to use sulphate and phosphate membrane transporters to penetrate microbial cells, this work reports on an initial study related to the effect of these oxyanions on Cr(VI) removal by an actinobacterium, Streptomyces sp. MC1. Aspects related to growth and pleomorphism of this strain under Cr(VI) exposure are also presented. Although this strain was able to remove Cr(VI) from a liquid medium, significant decreases in both growth and filament branching were observed under metal exposure. The presence of sulphate and phosphate ions in the culture medium did not reverse the Cr(VI)-induced morphological transition. However, both ions mitigated the inhibitory effect of Cr(VI) on bacterial growth, and increased their removal from culture supernatants. Since total chromium concentration in the supernatant remained constant, this finding may indicate that sulphate and phosphate ions play a key role in the external reduction of Cr(VI) by Streptomyces sp. MC1, and that therefore Cr(VI) bioremoval could be optimized in terms of time and cost.